TINDAKAN KEPOLISIAN DALAM MENANGANI PELAKU YANG MELAKUKAN TABRAK LARI (STUDI KASUS DI WILAYAH HUKUM POLRESTA DENPASAR) - Ari Subagia; Ni Luh Gede Yogi Arthani (Jurnal Hukum Mahasiswa, 2021)
Traffic accidents can occur as a result of someone's negligence or due to someone's non-compliance with traffic signs and / or signs. In this study, the authors focused research on hit-and-run traffic accidents. The hit and run was carried out by an irresponsible actor, by leaving the victim without stopping his vehicle. Furthermore, in the case of a hit-and-run traffic accident, the researcher took the object of research at the Denpasar Police Traffic Police Office. Based on data from the Denpasar Police Traffic Traffic Unit, there are numbers of hit-and-run traffic accidents from 2018 to 2020 with details in 2018 a total of 126 cases, 117 in 2019, and 107 in 2020. An important issue to be discussed further is how the role of the police in obtaining evidence in the crime scene in the Denpasar Police jurisdiction and what are the factors that strengthen that the case was indeed a hit and run. The theoretical basis used is the theory of authority, theory of evidence and theory of law enforcement. In this study, contains empirical legal research using descriptive research and using qualitative data analysis. The role played by the police in finding evidence at the scene of the hit-and-run traffic accident is still not optimal, this is because cases of traffic accidents that are caused by hit-and-run most of the cases are not resolved quickly because the police themselves experience a number of obstacles including relatively long investigation time, limited budget, limited personnel and minimal infrastructure. Factors that influence the truth of the hit-and-run case in a traffic accident case are influenced by facts in the field based on evidence at the crime scene, witness testimony and victim's testimony which are then analyzed and concluded. In addition, the police also use discretionary powers based on the Police Law, so that it can be concluded that the traffic accident was a hit-and-run or not.